Hydrogen peroxide induced cell death: One or two modes of action? - Lionel Uhl; Audrey Gerstel; Maialène Chabalier; Sam Dukan (Heliyon, 2015)
Imlay and Linn show that exposure of logarithmically growing Escherichia coli to hydrogen peroxide (H2O2) leads to two kinetically distinguishable modes of cell killing. Mode one killing is pronounced near 1 mM concentration of H2O2 and is caused by DNA damage, whereas mode-two killing requires higher concentration (>10 mM). The second mode seems to be essentially due to damage to all macromolecules. This phenomenon has also been observed in Fenton in vitro systems with DNA nicking caused by hydroxyl radical (HO•). To our knowledge, there is currently no mathematical model for predicting mode one killing in vitro or in vivo after H2O2 exposure. We propose a simple model, using Escherichia coli as a model organism and a set of ordinary differential equations. Using this model, we show that available iron and cell density, two factors potentially involved in ROS dynamics, play a major role in the prediction of the experimental results obtained by our team and in previous studies. Indeed the presence of the mode one killing is strongly related to those two parameters. To our knowledge, mode-one death has not previously been explained. Imlay and Linn (Imlay and Linn, 1986) suggested that perhaps the amount of the toxic species was reduced at high concentrations of H2O2 because hydroxyl (or other) radicals might be quenched directly by hydrogen peroxide with the concomitant formation of superoxide anion (a less toxic species). We demonstrate (mathematically and numerically) that free available iron decrease is necessary to explain mode one killing which cannot appear without it and that H2O2 quenching or consumption is not responsible for mode-one death. We are able to follow ROS concentration (particularly responsible for mode one killing) after exposure to H2O2. This model therefore allows us to understand two major parameters involved in the presence or not of the first killing mode.